Introduction to scholastic philosophy - "Wulf, Maurice De" (New York, 1956)
The object of the author is to meet and combat false conceptions, to coordinate true notions and so to finish the reader with some general information on the new scholasticism. The author has adopted quite a summary method. He has merely traced the outline, raised and stated the problems, but he does not claim to have noticed all the points of view which the subject matter admits of.
Keywords: Philosophy